Strategi Pengembangan Pariwisata Berkelanjutan (Sustainable Tourism Development) Berbasis Lingkungan Pada Fasilitas Penunjang Pariwisata di Kabupaten Badung - Ida Ayu Putu Widiati; Indah Permatasari (Kertha Wicaksana, 2022)
The objective of tourism development is not only to increase economic growth but also to preserve nature and surrounding environment. In the context as in the Regency of Badung, the problem arising is that there are still many tourism supporting facilities that are not in accordance with the zoning or designated area so they can have a negative impact towards the environment. This study examines the meaning of the concept of developing an environmentally-based sustainable tourism and strategies for developing the environmentally-based sustainable tourism in the area of tourism supporting facilities in Badung Regency. This study is of great importance in order to discover solutions in the form of appropriate strategies or policies for a sustainable tourism development. This study belongs to a empirical legal research that uses primary data and secondary data. The results of the study show that the concept of sustainable tourism development focuses on long-term tourism development minimizing negative impacts on the environment. The government has a strategic role in formulating relevant tourism development policies, especially in the process of planning as stated in the tourism development master plan in both the Province and Regency/City. The value of the philosophy of Tri Hita Karana is very appropriate to be applied in formulating policies for sustainable tourism development. In addition to formulating policies, a strategy for developing environmentally-based sustainable tourism in tourism supporting facilities in Badung Regency can be implemented by ensuring that all development is in accordance with its designation so as to reduce negative impacts on the environment. Empowerment of local communities in tourism development is also very important to be applied by holding the principles of religious and cultural values that live in the community as well as environmental sustainability.